Evaluation of Recording and Bookkeeping Applications in MSMEs Using the System Usability Scale Method - Anggraini, Ria; Herdianto, Arga Fawwaz; Awaliya, Qori Afifah Nur; Dewi, Citra; Darmawan, Arif (Pusat P2M Politeknik Negeri Batam, 2024)
This study employs a descriptive qualitative approach to evaluate the usability of the Bizpos application, developed by the Business Management Department of Batam State Polytechnic to address the technological needs of Micro, Small, and Medium Enterprises (MSMEs). Conducted as part of the Project Based Learning (PBL) program from November 2022 to June 2023, the research targeted active Bizpos users from micro and small businesses in Batam City. Data collection involved a survey technique utilizing the System Usability Scale (SUS) instrument, supplemented with suggestion items, with 10 selected respondents. Analysis was carried out descriptively, aided by descriptive and narrative techniques. Findings indicate proficient application utilization among respondents, with average scores exceeding 3 for each statement. The Bizpos application attained an